Pulmonary arterial hypertension: past, present and future - Aytekin, Metin; Caylak, Emrah (Turkish Assoc Tuberculosis & Thorax, 2010)
Pulmonary arterial hypertension (PAH) is a rare disease with incidence of approximately two to five per million per year and it is characterized by high pulmonary artery pressure. The mechanism of high blood pressure in pulmonary arteries is still unknown and also the pathogenesis of idiopathic PAH is not fully understood. Despite recent advances in therapy, PAH remains a progressive disease with high mortality and morbidity. Traditional hemodynamic markers of disease severity and progression have significant limitations and non-invasive markers are needed to guide follow-up and the effectiveness of therapy in idiopathic PAH patients. Our goal in this review is to give an overview of pulmonary hypertension and to provide researchers with a better understanding of this disease.
Pulmoner arteryel hipertansiyon: Dünü, bugünü ve yarini
Keywords: Pulmonary arterial hypertension; pathology; treatment; diagnosis